ANALYSIS OF FACTORS AFFECTING THE INDONESIAN SYARIAH STOCK INDEX (ISSI) ON THE INDONESIAN STOCK EXCHANGE (IDX) - Siska Angriani Hasibuan; Armin Rahmansyah (Quantitative Economics Journal, 2019)
The Indonesian Syariah Stock Index (ISSI) is an indicator that can be used by investors to know the movements of the sharia stock market. This research aims to analyze the effect of the Indonesian Syariah Stock Index (ISSI) on the Indonesian Stock Exchange (IDX). The analysis uses equations by the method of Error Correction Model (ECM). This study analyzed the relationship between the dependent and independent variables in both the short term and long term. Estimation results show that in the long term and the short term, the variable amount of the inflation was a positif and significant in the short term but not significant in the long term affect the Indonesian Syariah Stock Index (ISSI). The variable amount of the BI rate and exchange rate was a negative and significant in the short term but not significant in the long term affect the Indonesian Syariah Stock Index (ISSI). These results show that inflation, BI rate and exchange rate was significant in the short term affect the Indonesian Syariah Stock Index (ISSI) on the Indonesian Stock Exchange (IDX).